The Influence of Religiosity, Nationalism, and Tax Corruption Perception on Tax Compliance - Hani Hanifah; Ivan Yudianto (Universitas Padjadjaran, 2019)
This study aims to determine the effect of religiosity, nationalism, and perceptions of tax corruption on MSMEs taxpayer compliance in the area of Bandung City. This research used taxpayer awareness, moral obligation, and quality of tax service as factors. A questionnaire was used as research instruments in data collection. Respondents in this research were individuals who run businesses that belong to small and medium micro-enterprises. Multiple linear regression with SPSS program version 23 was applied for data analysis. The results of this study concluded that religiosity, nationalism, and perceptions of tax corruption simultaneously influenced significantly to taxpayer compliance. Partially test indicates the religiosity and nationalism have a positive effect on MSMEs taxpayer compliance, while the perceptions of tax corruption not affect taxpayer compliance.